Survei Minat Siswa Terhadap Olahraga Bulutangkis pada Siswa Kelas V - Maghfira, Maghfira; Saman, Saman; Jalil, Rasyidah (Universitas Hamzanwadi, 2025)
This study aims to determine students' interest in badminton in grade V students of SDN 13 Tappong Palopo. This research is a quantitative descriptive research with survey method. The population in this study were all grade V students of SDN 13 Tappong using saturated samples. with a total of 39 students. Data collection techniques in this study using questionnaires / surveys. Based on the results of research on overall student interest from 39 students of which in the very high category as many as 0 students (0%), high category as many as 21 students (53%), low category as many as 14 students (35%), very low category as many as 1 student (10.26%). So it can be concluded that students' interest in badminton in grade V students of SDN 13 Tappong Palopo is in the high category (53.85%). Students' interest in badminton sports for internal factors in the indicators of attention, liking, activities are mostly in the high category, namely 56.41%. Student interest in badminton sports for external factors in indicators of the role of teachers, facilities, and the environment is mostly in the high category, namely 61.55%. Based on the acquisition of data analysis, respondents expressed a high interest when learning badminton sports.